UPPER GASTROINTESTINAL ENDOSCOPIC ASSESSMENT OF PATIENTS PRESENTING WITH DYSPEPSIA - Khan, Nowshad; Shabbir, Ghulam; Zarif, Muhammad; Khattak, Muhammad Ishaq (Journal of Postgraduate Medical Institute, 2011)
Objective: To evaluate common causes of dyspepsia and to correlate endoscopic findings with histological examination of biopsy specimens. Material and Methods: This observational descriptive study was conducted at department of medicine Khyber Teaching hospital Peshawar, from 1st June 2006 to 31st December 2006. Detailed history, thorough physical examination and relevant investigations were done in each patient. All patients underwent upper gastrointestinal (GI) endoscopy. Biopsies were taken in every patient from oesophagus, stomach and duodenum. Histological examination was done from single pathologist. Results: The endoscopic findings of 50 patients with dyspepsia were studied. Out of 50 patients, 35(70%) were males while 15(30%) were females. Eighty two percent (41/50) were in the age group of 30-50 years. The most common presentations were epigastric pain in 45 (90%) cases, heartburn in 36 (72%) and flatulence in 35 (70%) cases. The endoscopic findings were normal in 25 (50%) patients. The abnormal findings included esophagitis in 6 (12%) patients, gastric ulcer in 5 (10%) patients, duodenal ulcer in 4 (8%) patients, gastritis in 4 (8%) patients and duodenitis in 2 (4%) patients; while esophagogastritis, gastroduodenitis, esophagogastroduodenitis and carcinoma stomach were present in 1 (2%) patient each. All the endoscopically abnormal as well as normal findings were confirmed by histopathology. Conclusion: The endoscopic findings were normal in majority of patients with dyspepsia. The common abnormal endoscopic findings included esophagitis, gastric ulcer, duodenal ulcer and gastritis. The endoscopic findings were matching with histological diagnosis.